2012
DOI: 10.1120/jacmp.v13i4.3753
|View full text |Cite
|
Sign up to set email alerts
|

An evaluation of the Clarity 3D ultrasound system for prostate localization

Abstract: The purpose of this study is to evaluate the accuracy and precision of the Clarity 3D ultrasound system to track prostate gland positional variations due to setup error and organ motion. Seventeen patients (n=17) undergoing radical external beam radiation therapy for localized prostate cancer were studied. Subsequent to initial reference ultrasound and planning CT scans, each patient underwent seven repeat weekly tracking CT and ultrasound (US) scans during the course of treatment. Variations in the location o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
31
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(34 citation statements)
references
References 20 publications
3
31
0
Order By: Relevance
“…Direct imaging of the prostate gland and daily verification of its position during each treatment session is essential for reducing the margins and, consequently, avoiding the organs at risk such as rectum and bladder. Several image guidance methods have been investigated in recent years, including tumor tracking with intraprostatic fiducial markers, cone‐beam computed tomography (CBCT), and ultrasound‐based imaging (US‐image guidance) 1 , 2 , 3 , 4 , 5 , 6 , 7 , 8 . Ultrasound‐based systems are volumetric and offer better soft‐tissue visualization compared to CBCT, without additional exposure to ionizing radiations (9) .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Direct imaging of the prostate gland and daily verification of its position during each treatment session is essential for reducing the margins and, consequently, avoiding the organs at risk such as rectum and bladder. Several image guidance methods have been investigated in recent years, including tumor tracking with intraprostatic fiducial markers, cone‐beam computed tomography (CBCT), and ultrasound‐based imaging (US‐image guidance) 1 , 2 , 3 , 4 , 5 , 6 , 7 , 8 . Ultrasound‐based systems are volumetric and offer better soft‐tissue visualization compared to CBCT, without additional exposure to ionizing radiations (9) .…”
Section: Introductionmentioning
confidence: 99%
“…Ultrasound‐based systems are volumetric and offer better soft‐tissue visualization compared to CBCT, without additional exposure to ionizing radiations (9) . Several studies have shown that US‐based IGRT represents a reliable system for image guidance; 3 , 7 , 8 various other technical solutions may be used for ultrasound IGRT in clinical practice, either based on intramodality or cross‐modality verification methods (3) . Concerning other image guidance methods, optimal imaging may depend on the operators' experience 10 , 11 …”
Section: Introductionmentioning
confidence: 99%
“…The BAT® [12] (Nomos, Pittsburg, USA) and SonArray® [13] (Varian, Palo Alto, USA) devices are based on an inter-modality registration that consists of projecting the CT contours on the US treatment image to determine target misalignments. In contrast, the Clarity device (Elekta, Stockholm, Sweden) is an intramodality system that compares a daily TA-US image acquired at the beginning of the treatment session to a reference TA-US image acquired during the planning CT acquisition [6][7][8][9][10][11]. Three studies have reported results on the accuracy of the Clarity TA-US system in clinical conditions.…”
Section: Introductionmentioning
confidence: 90%
“…Furthermore, the use of FM requires an X-ray imaging modality, such as megavolt electronic portal imaging (MV-EPI) or kilovolt projection imaging. The second category encompasses imaging modalities enabling a 3D acquisition such as CT-on-rails, cone beam computed tomography (CBCT), cine magnetic resonance imaging and ultrasound (US) imaging [6][7][8][9][10][11][12][13]. Among these modalities, CBCT is the most used.…”
Section: Introductionmentioning
confidence: 99%
“…This is why fused multimodality data sets are frequently used for contouring. Several imaging methods can be used in combination with CT for better localization and definition of the prostate: the most common are cone-beam computed tomography (Oldham et al 2005;Zeng et al 2008), magnetic resonance imaging (MRI) (Raaymakers et al 2009) and ultrasound (US) imaging (Fraser et al 2010;Fung et al 2006;Lattanzi et al1999;Mayyas et al 2013;Morr et al 2002;Robinson et al 2012;Wein et al 2007). US is currently mostly used for segmentation and IGRT (Molloy et al 2004;Smith et al 2007) because it provides a quantitative and cost-effective imaging technique that avoids unwanted radiation dose to the patient.…”
Section: Introductionmentioning
confidence: 99%